Facile synthesis of low-cost biomass-based γ-Fe2O3/C for efficient adsorption and catalytic degradation of methylene blue in aqueous solution. Issue 1 (23rd December 2016) - Chen, Tao; Xiong, Yuhao; Qin, Yuemei; Yang, Haiguan; Zhang, Peng; Ye, Fanggui
Abstract : In this study, a novel and low-cost method was developed for synthesizing magnetic porous γ-Fe2 O3 /C as an adsorbent and catalyst for removal of methylene blue (MB) from aqueous solution. Abstract : In this study, a novel and low-cost method was developed for synthesizing magnetic porous γ-Fe2 O3 /C as an adsorbent and catalyst for removal of methylene blue (MB) from aqueous solution. Using FeCl3 ·6H2 O and bagasse as the precursor, the biomass-based material was synthesized rapidly using a microwave heating process. Fe ions were introduced to achieve both adsorption and catalytic degradation by the Fenton reaction. Characterization by BET, XRD, SEM, and TEM indicated that the prepared γ-Fe2 O3 /C material exhibited homogeneous mesoporosity with a BET surface area, mesoporous volume, and saturation magnetization of 764.116 m 2 g −1, 0.54 cm 3 g −1, and 17.1 emu g −1, respectively. The material exhibited excellent adsorption and catalytic degradation abilities for removal of MB from aqueous solution (up to 352.96 mg g −1 ), with complete degradation of MB within 30 min. Moreover, γ-Fe2 O3 /C had good stability over 5 cycles. Therefore, this biomass-based γ-Fe2 O3 /C material can be used as a highly effective and low-cost adsorbent and catalyst and has great potential application in clean-up processes for environmental pollutants.